Perlindungan Hukum bagi Masyarakat Hukum Adat Adonara yang Melakukan Perjanjian Gadai Tanah (Gerang Ekan) Tanpa Perjanjian Tertulis - Filgentius Xander Laga; Umbu Yanri Aryanto Fallo; Antonius Revilno Konseng Dacunha; Stefanus Don Rade (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
Agreements in Indonesia: Each region has a special name or customary term to describe the agreement, however, each agreement term has the same meaning. Article 1338 of the Civil Code states that "For the parties involved, every valid agreement has legal force. An agreement can only be revoked with the consent of both parties or for reasons determined by law, which require that the agreement be carried out in good faith." Every agreement made in various regions of NTT must be agreed upon. The party implementing the agreement is the party implementing the agreement, and if there is a party who does not implement the agreement in accordance with the agreement, then the party who violates the agreement must also bear the responsibility concerned. The method used is the Empirical Legal Research Method. The research results show that the implementation of land pawning was carried out by Adonara and the customary law community. The implementation of Amanuban NTT is essentially already underway. agree with what they believe. based on mutual trust and the place of pawning is usually between families and based on family deliberation and land pawning is usually carried out because of life's necessities in general related to economic and educational issues. The agreement reached is stated in written or unwritten form, but generally it is not written and is binding on both parties. An agreement can also be considered to meet the requirements if it complies with the provisions of Article 1320 of the Civil Code. Land mortgage rights in customary law communities are also applied in customary law communities because the procedure is fast, simple and not complicated. Compared to applying to a bank, the customary land pawning system is actually faster and simpler because land pawning can be done at any time in customary law communities.